The distribution of the growth dividends - Hermansen, Mikkel (OECD Publishing, 2016)
Widespread increases in inequality over the past three decades have raised the question of the distribution of the growth dividends. This paper finds that there is no single answer to this question. The mechanisms that link growth and income inequality are found to differ depending on the sources of growth and on whether one considers income inequality before or after government redistribution, that is, inequality in market incomes, i.e. income derived before taxes and transfers, or inequality in disposable incomes, that is, income after taxes and transfers. Labour productivity growth is found to have contributed to rising market income inequality, while this was partly mitigated through government redistribution, on average across OECD countries over the last decades. By contrast, employment growth is found to have had an equalising impact, benefiting mostly the households in the lower part of the income distribution. These two forces tended to offset each other and resulted in a broadly distribution-neutral impact of GDP per capita growth, on average across OECD countries over the last three decades. While inequality has risen in many countries, this would tend to suggest that factors other than GDP growth itself have been driving widening income gaps between rich and poor households
Keywords: Economics